1989
DOI: 10.1177/104649648902000105
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related To Group Cohesiveness

Abstract: This article investigates the relationship of group cohesiveness to empathy, self-disclosure, acceptance, and trust, and compares three different groups (personal growth groups, DUI groups, and psychotherapy groups) on measures of cohesiveness. Three hypotheses are tested, using 65 group members divided into the three subgroups. As hypothesized, personal growth groups showed a significantly higher level of cohesiveness. All factors examined correlated significantly with cohesiveness and with one another. Trust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 15 publications
1
24
0
2
Order By: Relevance
“…Additionally, several researchers have found that children and youth exposed to chronic community violence are at risk for academic problems, such as poor achievement and grade retention~Mazza & Overstreet, 2000!. In contrast, safety and trust contributes positively to intimacy within a group, and is a factor that underlies adolescent willingness to engage in community action~McLaughlin, Irby, & Langman, 1994;Roark & Sharah, 1989!.…”
Section: Neighborhood Resources and Safetymentioning
confidence: 95%
“…Additionally, several researchers have found that children and youth exposed to chronic community violence are at risk for academic problems, such as poor achievement and grade retention~Mazza & Overstreet, 2000!. In contrast, safety and trust contributes positively to intimacy within a group, and is a factor that underlies adolescent willingness to engage in community action~McLaughlin, Irby, & Langman, 1994;Roark & Sharah, 1989!.…”
Section: Neighborhood Resources and Safetymentioning
confidence: 95%
“…Cohesiveness is a key theoretical construct to describe the ''group-ness'' of individuals constituting an interactive small team (Hogg, 1992;Shaw, 1980). As individuals extend their trust to others, they create a work environment that is characterized by mutual empathy, a willingness to accept others, and a high level of cohesiveness (Roark & Hussen, 1989). This high level of cohesiveness, in turn, leads to the members' deep identification with a team (Roark & Hussen 1989).…”
Section: Effect Of Trust On Cohesivenessmentioning
confidence: 99%
“…Worker solidarity is a key concept in the sociology of work (Hodson 2001). Social psychologists have repeatedly returned to issues surrounding cohesion and solidarity, attempting to understand both its nature (Bollen and Hoyle 1990;Gross and Martin 1952;Roark and Shara 1989) and consequences (Carron 1982;Hansell 1984).…”
Section: Structural Cohesion and Embeddedness: A Hierarchical Conceptmentioning
confidence: 99%